The Association of HIV and Syphilis among Men Who Have Sex with Men: An Integrated Biological and Behavioral Survey - Indriani, Dine Dyan; Sudaryo, Mondastri K. (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Increasing rates of syphilis in diverse geographical settings demand that people should have a heightened awareness of syphilis, especially in high-risk patients, including those who are MSM contracting HIV-positive. This study aimed to assess the association of HIV and syphilis among men who have sex with men (MSM) in Depok and Bogor using an Integrated Biological and Behavioral Survey 2018/2019. A cross-sectional study was conducted involving 750 eligible participants. Inclusion criteria: MSM living in study location, aged over 15, and had sexual relations with men at least once in the previous year. A prevalence ratio was obtained through multivariate Cox regression analysis. This study found that 11.3% of subjects were identified as having syphilis, and 20.1% were declared positive for HIV. The final model evidence a PR value of 2.46; 1.59-3.81 with a p-value of 0.00 for the risk of MSM infected with HIV to develop syphilis. Overall, HIV has a statistically significant relationship with the incidence of syphilis after being adjusted by the use of condoms with non-permanent partners and STI screening. Integrated intervention techniques, HIV testing, and enhanced awareness are required to reduce HIV, syphilis, and co-infection; targeting MSM and other vulnerable groups is in urge.